Total quality control - Feigenbaum, Armand V. (McGraw-Hill, 1991)
This is a text on achieving profitability through quality, updated for the global marketplace of the 1990s. Principles are put into practice and the two critical success factors are fully explored: how to build quality controls into every phase of operations - product and service development, production, engineering, marketing, distribution, sales, customer service; and how to drive communication and the implementation of quality control strategies down and across organizational lines, mobilizing commitment at every level